2019
DOI: 10.1097/md.0000000000014969
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the management of coronary artery bypass graft only on moderate ischemic mitral regurgitation

Abstract: To summary the impact of off-pump coronary artery bypass grafting (CABG) only on patients with moderate ischemic mitral regurgitation and survival.We retrospectively analyzed 109 patients with coronary artery disease (CAD) complicated by moderate mitral regurgitation, from January, 2008 to December, 2014, in the Department of Cardiovascular Surgery at the No. 2 Hospital of Jilin University undergoing off pump CABG only. Preoperative clinical characteristics, complications after surgery, and outcome (survivor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…5,6 This may be due to racial and genetic reasons. Approximately one week (8 days) hospital stay was observed among 79% (n=54) of the patients in our study, and similar days of hospital stay after the surgery were observed in the study of Wang et al 7 There were 88.24% (n=60) males included in our study, which is higher in numbers than females.…”
Section: Discussionsupporting
confidence: 88%
“…5,6 This may be due to racial and genetic reasons. Approximately one week (8 days) hospital stay was observed among 79% (n=54) of the patients in our study, and similar days of hospital stay after the surgery were observed in the study of Wang et al 7 There were 88.24% (n=60) males included in our study, which is higher in numbers than females.…”
Section: Discussionsupporting
confidence: 88%
“…[6][7][8][9][10][11][12][13] While these therapies improve symptoms, exercise capacity, hemodynamics, and functional status, as well as reduce hospitalizations and delay disease progression, 1,8 PAH remains a chronic, progressive, and incurable disease. 14,15 Functional class (FC) is widely used as a clinical end point in studies of cardiovascular diseases, including heart failure, 16 coronary artery disease, 17 and congenital heart disease. 18 In patients with PAH, FC is strongly associated with survival and is considered to be an essential component of risk assessment and treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Functional class (FC) is widely used as a clinical end point in studies of cardiovascular diseases, including heart failure, 16 coronary artery disease, 17 and congenital heart disease 18 . In patients with PAH, FC is strongly associated with survival and is considered to be an essential component of risk assessment and treatment planning 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%